The alkyl linkers in tandem-homodimers of a β-sheet-forming nonapeptide affect the self-assembled nanostructures. Issue 11 (1st June 2016) - Tomizaki, Kin-ya; Tanaka, Atsushi; Shimada, Hiroki; Nishizawa, Koki; Wada, Tsubasa; Imai, Takahito
Graphical abstract: Abstract: There is increasing interest in designing smart biomaterials by employing the self-assembly characteristics of synthetic peptides. The use of amyloid-like fibrils is one approach to nanometer- and micrometer-sized supramolecular structures. However, it is generally difficult to predict and/or analyze peptide conformations in nanostructures generated by the self-assembly of β-sheet-forming peptides such as amyloid-β peptide because each peptide experiences a slightly different environment. Therefore, a methodology for rationally designing peptide-based smart materials is required. In this study, we demonstrate the design and synthesis of tandem-homodimers of a β-sheet-forming peptide where the amino acid sequence is duplicated in series and joined via alkyl linkers of different chain length. The conformations of these tandem-homodimers within the self-assembled nanoarchitectures in aqueous solution were characterized. Our findings demonstrate that the hydrophobicity and/or flexibility of the alkyl linkers significantly affect the peptide conformation (extended or bent) of the self-assembled peptide nanostructures. We believe that the present tandem-homodimerization method represents a new direction for the rational design of peptide-based smart biomaterials.